REVASCULARIZATION OF LATE-PRESENTING ACUTE LIMB ISCHAEMIA AND LIMB SALVAGE - Khan, Muhammad Iqbal; Nadeem, Irfan Ahmed (Journal of Ayub Medical College Abbottabad, 2016)
Background: Late-presenting acute limb ischaemia represents a challenging vascular emergency. The purpose of this study was to evaluate the outcome in patients following revascularization and management of existing or impending reperfusion injury of ischaemic limbs over a 12-year period (2002-2014). Methods: Routine procedural codes were used to label consecutive patients admitted 72 hours following onset of symptoms for surgical revascularization of an acutely ischaemic limb. Data collected included demography, clinical presentation, synchronous morbidities, procedural specifics and outcomes of surgical management of all patients. Results: The study sample included 206 patients, (117 male and 89 female, average age =49.4±14.6 years) presenting with a diagnosis of acute limb ischemia. The most frequent cause of acute thromboembolic limbs was cardiac disease (n=148). Femoral artery exploration with embolectomy was the most common procedure and was used for aortic, iliac, infrainguinal and distal occlusion. Thirty-four patients required additional vascular surgery due to failure of revascularization by embolectomy. Fasciotomy was performed in 45.6% of cases for existing or impending compartment syndrome when the patient presented very late. Surgical site infection occurred in 8.25% of cases, repeat embolectomy was required in 10.68% of cases; amputation in 13.1% and mortality was 5.8%. Predictors of morbidity and mortality included age of the patient, time of presentation and specific comorbidities. The 5-year amputation-free and survival estimate was 80%. Conclusion: Our study suggests that late revascularization of acute leg ischaemia improves blood supply to the limb, thereby reducing the number of amputations. The results suggest that revascularization is clinically warranted, even one week following the onset of acute ischaemia. Additional surgical procedures including fasciotomy further reduce the morbidity and mortality. Keywords: Acute ischaemia, revascularization, embolectomy, fasciotomy, amputation, reperfusion injury, compartment syndrome